SARS-CoV-2 VIRUS AND PERIODONTITIS - Sánchez-Cárdenas, Mayté (2021)
Several scientific articles have proposed hypotheses to associate the disease caused by the SARS-CoV-2 virus with periodontitis. Delving into the possible risk factors and indicators are essential elements to understand the role of the virus in the pathogenesis of periodontitis; they indicate the need for a joint work of physician and periodontologists in the protocol for the prevention and control of COVID-19. The relationship between these diseases is considered to be bidirectional, the effect of the virus on the immune system can aggravate periodontitis and, on the other hand, the effects of chemical mediators of periodontitis can make the patient more vulnerable once infected by SARS-CoV -2 to develop a co-infection. Key words: COVID-19 - periodontitis - SARS-CoV-2 - virus